Intrapreneurial competencies: development and validation of a measurement scale. Issue 1 (3rd July 2017) - Vargas-Halabí, Tomás; Mora-Esquivel, Ronald; Siles, Berman
Abstract : Purpose: Few models have attempted to explain intrapreneurial behavior from the perspective of competencies. Therefore, the purpose of this paper is to contribute along this line by developing and validating a scale to measure intrapreneurial competencies for a Costa Rican organizational context. Design/methodology/approach: A three stage process was followed. The first stage considered literature review, expert judgment, cognitive interviews, and back-translation. In the second stage, the questionnaire was administered to a sample of 543 university professionals who worked mainly in private organizations in Costa Rica. The third stage led to evaluate of the proposed scale's psychometric properties, including, exploratory factor analysis procedure performing by SPSS 19; confirmatory factor analysis procedures by means of structural equation modeling using EQS 6.2 version and finally, a linear regression model to obtain evidence of external criterion-related validity, performed by SPSS 19. Findings: This study provides evidence of five sub-dimensions of employee attributes, i.e., "opportunity promoter", "proactivity", "flexibility", "drive", and "risk taking" that constitute a higher-level construct called intrapreneurial competencies. The scale provided evidence of convergent, discriminant, and criterion-related validity – the latter, using an employee innovative behavior scale. Originality/value: The model offers a first step to continue studies that aim at developing a robust model of intrapreneurial competencies. This potential predictive capacity of an instrument of this nature would be useful for the business sector, particularly as a diagnostic instrument to strengthen processes of staff development in areas that promote the development of innovation and the creation of new businesses for the company.